Evaluating the Concept of Oral Manifestation of Thalassemia Major and Its Dental Consideration: A Report on Two Cases and a Literature Review - Nidhi Yadav; Ajay Parihar; Prashanthi Reddy; Arun D Sharma (Journal of South Asian Association of Pediatric Dentistry)
Background: Thalassemia is one of the most prevalent inherited diseases in the world, posing public health and societal challenges in high-risk locations. Thalassemia can be classified into two types—α-thalassemia and β-thalassemia, which are caused by abnormalities in the synthesis of hemoglobin (Hb) α- or β-polypeptide chains. Reduced synthesis of one of the two globin polypeptides leads to diminished Hb production, resulting in hypochromic microcytic anemia with erythrocyte dysplasia and destruction. The case reports presented and evaluated here show distinctive orofacial features, classic radiographic features, and dental considerations in thalassemia major patients. Conclusion: Thalassemia major causes several orofacial and systemic problems, which worsen with age. Early diagnosis and management result in a better prognosis and decreased morbidity. Clinical significance: Dental practitioners, particularly those working in multiracial populations, need to comprehend the disease's complications and therapy.